Analysis of cases with tuberculous peritonitis: A single-center experience - A. Cumhur Dülger,; Sevdegül Karadaş,; Rafet Mete,; M. Kürşat Türkdoğan,; Davut Demirkıran,; Bilge Gültepe, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Tuberculous peritonitis (TP) is a rare form of tuberculosis and is caused by peritoneal involvement with Mycobacterium tuberculosis. A distinctive correlation exists between socioeconomic state and disease prevalence. We aimed to evaluate the clinical, laboratory, and radiological ﬁndings of patients with TP. Materials and Methods: We conducted a retrospective study in patients with peritoneal tuberculosis from January 2004 to October 2008 at Yuzuncu Yil University Medical School Education and Research Hospital. During this time, the data of 21 patients (17 females) with TP were reviewed. Results: Fever, abdominal pain, and anorexia were the most common symptoms. An analysis of ascites showed lymphocyte predominance and low albumin gradient in all patients. Patients with TP had a median ascites adenosine deaminase (ADA) level of 139 U/L (range, 25 to 303U/L). Peritoneal involvement (wet peritonitis) was seen in all the cases. Following 6-month administration of combined anti-TBC treatment, mean serum CA-125 levels were within the normal range among patients who had previously higher serum CA-125 level. Mortality rate in the total cases was 4.6%. Conclusion: Peritoneal tuberculosis should be considered in the differential diagnosis of exudative ascites in eastern Turkey. A high level of suspicion is required, especially in high-risk populations living in rural areas. ADA seems to be a sufﬁcient, safe, and inexpensive method to perform the diagnosis of peritoneal tuberculosis. Serum CA-125 levels may play a key role to support the diagnosis as well as disease management of TP. Turkish Başlık: Tüberküloz peritonit olgularının analizi: Tek merkez deneyimi Anahtar kelimeler: Tüberküloz peritonit, adenozin deaminaz, Doğu Anadolu, serum CA-125 Arkaplan/Amaç: Tüberküloz peritonit (TP) tüberkülozun nadir bir formudur ve etken Mycobacterium tuberculosisdir. Hastalık prevalansı ve sosyoekonomik durum arasında belirgin bir korelasyon vardır. Çalışmamızda TP’li hastaların klinik, laboratuvar ve radyolojik bulgularının değerlendirilmesi amaçlanmıştır. Yöntemler ve Gereçler: Yüzüncü Yıl Üniversitesi Tıp Fakültesi Eğitim ve Araştırma Hastanesi'nde Ocak 2004- Ekim 2008 tarihleri arasında TP tanısı alan 21 olgunun sosyodemografik, klinik ve radyolojik verileri retrospektif olarak incelendi. Bulgular: Bu zaman ölçeği olarak olguların 17 kadın ve 4 erkek oluşmuştu toplam olguların yaş ortalaması 30 (18-60 yaş) idi. Ateş, karın ağrısı ve iştahsızlık en sık görülen semptomlardı. Asit analizi lenfosit hakimiyeti ve tüm hastalarda düşük albumin gradiyenti gösterdi. TP hastalarında asit adenozin deaminaz (ADA) düzeyi ortalaması 139 U/L (25-303 U/L) idi. Periton tutulumu tüm vakalarda saptandı. Altı aylık combine anti tüberküloz tedavi takiben, başlangıçta yüksek olan serum CA-125 düzeyleri hastaların tümünde ile normale döndü. Mortalite oranı % 4.6 saptandı. Sonuç: TP Doğu Anadolu Bölgesi’nde eksuda nitelikli asitlerin ayırıcı tanısında göz önünde bulundurulmalıdır. Kırsal kesimde yaşayan ve yüksek riskli populasyonda yüksek şüphe indeksi gereklidir. TP tanısında ADA ucuz ve güvenli bir tanı yöntemi olabilir. Serum CA-125 düzeylerinin TP tanı ve tedavisinde önemli rolü vardır.